Characteristics of an elite swimming start - Tor, E.; Pease, D. L.; Ball, K. A. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
In competitive swimming, the start has been strongly linked to overall performance (Cossor & Mason 2001), The swimming start can contribute between 0.8-26.1% of total race time depending on the distance (Lyttle & Benjanuvatra 2005), with the percentage contribution increasing as the distance of the race becomes shorter (Hay 1986). The swimming start phase of a race is defined as the time from the starting signal to when the centre of the swimmer's head reaches 15 m (Cossor & Mason 2001). The start as a whole is typically broken into three sub-phases: the on-block, flight and underwater phases. The percentage time contribution of each sub-phase is approximately 11%, 5% and 84% respectively (Siawson, Conway, Cosser, Chakravorti & West 2013). The on-block phase is described as the time from the starting signal to when the swimmer leaves the block while the flight phase is the time from when the swimmer leaves the block to when the swimmer enters the water. The last and longest phase of the start is the underwater phase and is the time from when the swimmer enters the water to when the swimmer resurfaces to begin free swimming. The free-swimming time is defined as the time following the underwater phase from breakout to 15 m. Following the Beijing Olympics in 2008 a new starting block was introduced to international competition. The Omega OSB11 starting block has an adjustable kick plate, footrest or back plate fixed at 30° which can be moved to five different locations (35 mm intervals) along the length of the starting platform which is also angled at 10° to the horizontal. As a result of the introduction of these blocks a different starting techniquecalled the 'kick-start' has been developed and utilised by most elite swimmers during competition. Multiple research studies have found that swimmers can gain an added advantage using this new technique (Honda, Sinclair, Mason & Pease 2010; Takeda, Takagi & Tsubakimoto 2013). This is mainly due to an increase in horizontal velocity with the added contribution of the increased force that is able to be produced by the rear leg (Honda et al. 2010). There have been many previous start studies that have compared different start techniques (Bianksby, Nicholson & Elliott 2002), or evaluated different elements of the start such as foot placement (Takeda et al. 2013), entry angle (Groves & Roberts 1972) and starting position (Honda, Sinclair, Mason & Pease 2012). Although these studies have used elite/sub-elite subjects the groups they used were mixed and comparisons between genders were not made. Cesser and Mason (2001) did separate their analysis into male and female groups, however they did not make comparisons between gender. Furthermore, Seifert et al. (2010), Vantorre et al. (2010), Breed et al. (2000), Kirner et al. (1989) examined start performance based only on low-to moderate numbers of single gender subjects. There is obvious strength, performance and technical differences present for males compared to female swimmers so combining genders in the same analysis may not be appropriate, as differences might exist in how velocity is developed. The same observations can be made when comparing start performances for difference strokes. There are even fewer studies that have combined different strokes in their study design. Only two known studies have compared the differences between freestyle and butterfly starts. Strojnik et al. (1998) found small differences in the flight phase of the start, while Whitten (1997) found that butterfly swimmers travelled deeper during the underwater phase. However, these studies compared the differences between strokes using a grab start technique. Given that the grab start has been superseded by the kick-start, the findings from these studies may not be relevant to techniques currently used in competition. This study is the first to compare start performances and specific start parameters between male and female using elite swimmers and the new kick-start technique. The aims of this study were to characterise the swim start of elite swimmers using the new Omega OSB11 starting block and to make comparisons between gender and different strokes based on overall start performance.